Internalization of Multicultural Education Values in Fiqh Learning at Madrasah Aliyah - Afrian, Nurfahmi; Hakim, Dian Mohammad; Mustafida, Fita (Southeast Asian Journal of Islamic Education, 2025)
This study aims to examine the process of internalizing multicultural education values in Islamic jurisprudence (fiqh) learning at MA DDI Darun Najah Kaloling, situated within a multiethnic community. The research focuses on planning, teacher strategies for internalization, and evaluation and its impacts on students. The subjects of this study were the Head of the Madrasah, the Fiqh subject teacher, and students. A qualitative approach was employed, using interviews, observations, and documentation, with data analyzed through collection, condensation, presentation, and verification stages. Data validity was ensured through triangulation of sources, techniques, and time. The findings reveal that multicultural value internalization was systematically carried out through the synergy of institutional policies, curriculum enhancement, and teacher training. The madrasah’s vision, which emphasizes Qur'anic character and religious moderation, served as a foundation for instilling tolerance values. Teachers applied a phased strategy of transformation, transaction, and transinternalization using active learning approaches such as discussions and case studies. Evaluation indicated improved tolerant attitudes, a more inclusive classroom environment, and reduced conflict potential. These findings produced an internalization model that can serve as a reference for other madrasahs in fostering a multicultural and harmonious learning environment. This indicates that multicultural education can be effectively integrated into religious instruction. A holistic educational design is needed, encompassing policy, instructional strategies, evaluation, and teacher training alongside further research to explore broader contexts and identify enabling and inhibiting factors in the internalization of multicultural values across diverse madrasah settings.